Human appropriation of net primary production in Finland during 1990–2010. (December 2015) - Saikku, Laura; Mattila, Tuomas; Akujärvi, Anu; Liski, Jari
Abstract: Land-use environmental impacts are gaining attention as global demand for land is increasing. Human appropriation of net primary production (HANPP) is a useful measure to estimate how much of the net primary production (NPP) available for ecosystem processes is appropriated by humans annually. It accounts for the NPP extracted by biomass harvest, and the NPP losses due to land conversion. Finland is a forested country with good availability of detailed data for calculating HANPP. We estimated HANPP for Finland for a period from 1990 to 2010. Human appropriation of net primary production in Finland was on average 59% of the potential net primary production during the 1990's and then decreased fairly steadily to 50% in 2010. Net primary production harvested by humans, HANPPharv, remained fairly constant over the study period, on average 25 Mt carbon. HANPP due to land use change (HANPPluc ) decreased from 50 Mt to 38 Mt carbon during the past 20 years. The difference between the actual NPP of forests and the potential NPP without any human intervention decreased, mainly due to the growth of wood biomass stock in forests yielding larger amounts of litter production and further larger NPP. Forest HANPPluc, however contributed as much as 50% of the Finnish total HANPP in 2010. Our study shows for the first time the importance of calculating potential NPP for forests in detail. Highlights: Human appropriation of NPP (net primary production) decreased in Finland 1990–2010. Harvested NPP in Finland did not increase much during the study period. Losses of NPP due to land conversion in forestry dominated the impacts and decreased. This was mainly due to the growth of wood biomass stock resulting in increasing NPP. Relatively, 50% of the potential NPP was appropriated in 2010.